A Preliminary Study on Avian Diversity at the New City of Kemayoran Airport, Jakarta - Yeni A Mulyani; Ani M Pakpahan (Department of Forest Resources Conservation and Ecotourism - IPB University, 1993)
The objective of this study was to reveal the avian divesity at KBBK through direct and indirect obsemtion. Based on a 3 day obsemtion, we found 50 species of birds, consisted of 17 specieswaterbirds, 4 species of marsh birds, 1 species of shorebirds and 28 species of temstrial birds. The species richness was greatly reduced compared to the conditions in 1990 and 1991.